Islamic Economic Systems and Principles and Their Challenges in the Modern World - Kartika; Amiruddin (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to explore the application of the Islamic economic system in the context of the modern global economy, as well as to identify the challenges and opportunities faced in the integration of Islamic economic principles with the capitalist system. The research method used is a qualitative descriptive approach with content analysis of relevant literature, including books, articles, and research reports related to Islamic economics, zakat, Islamic banking, and fintech. The results of the study indicate that although Islamic economic principles, such as the prohibition of usury, avoidance of maisir and gharar, and redistribution of wealth through zakat, offer solutions to social inequality, the main challenge lies in integration with the global market dominated by capitalism. However, the Islamic banking sector and sharia-based fintech show great potential in expanding financial access and improving social welfare, providing opportunities for the development of a more inclusive and sustainable Islamic economic system.